Being Thomas Jefferson : an intimate history - Burstein, Andrew (Bloomsbury Publishing, 2026)
The deepest dive yet into the heart and soul, secret affairs, unexplored alliances, and bitter feuds of a generally worshipped, intermittently reviled American icon.